The Strategies in Dealing with Political Conflict in Syria: Study of Khalid Khalifah’s La Sakakin Fi Mathabikhi Hadzihil-Madinah - Arief Budiman (Humaniora, 2016)
Novel La Sakakin fi Mathabikhi hadzihil-Madinah (LSMHM) is considered to have an intense ideological and political nuance for its narration on conflict. It is worth reading this novel to observe the measures chosen by the characters in dealing with existing conflict and its impacts. Sociological approach to literature is applied to reveal the strategy. The reading reveals that the characters in this novel have various strategies in dealing with conflict and related problems. Contending, yielding, problem solving, withdrawing, and inaction are the possible strategies. However, none of the characters choose yielding or problem solving. The existing preferences seem to be the writer’s outlook on that conflict. The conflict itself has been inflicting refuge, social manipulation, excision, and harassment.